A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 5 - However emphatic the government's spokesmen may be in their protestations of the value of the voluntary hospital in any national health service, and of the importance of their survival as autonomous bodies, there is no evidence to lead one to suppose that this view would be shared by local authorities. The government's proposals provide for the local authorities to have complete control of the provision of hospital services and of the arrangements for the consultant service and to make payments for such services as they may require, voluntary hospitals to perform under contracts. Under such arrangements the local authorities could exercise an influence on the voluntary hospitals' expenditure and, by encouraging a tendency to regimented standardisation, preclude that complete freedom in the treatment of their patients by the medical staff which is the most effective and distinctive feature of the voluntary hospital system and is vital for the wellbeing of the patient; could hamper their work in Medical Research, which has ever been regarded as one of the principal features of the service rendered by the voluntary hospitals to the nation; could in time cancel contracts with individual voluntary hospitals, thereby threatening or terminating their very existence. It may of course be said by some that such possibilities are remote and never likely to occur, and that the voluntary hospitals are unreasonably apprehensive. The fact remains that there is no guarantee that they will not occur. Local authorities are constantly changing bodies, elected according to the trend of political opinion, and with correspondingly changing ideas. It is, too, an ominous and significant fact that, in certain quarters, inimical to the voluntary hospitals, satisfaction is already being expressed that these hospitals will come under local government control. Can this indicate anything but the expectation, if not the intention, that the wide powers of the Joint Authority may be used, at best to restrict the freedom and autonomy of the voluntary hospital, at worst to secure its gradual disappearance or absorption? 10. - General Conditions Precedent to Participation It is for these reasons that as a condition precedent to their participation in the scheme, the voluntary hospitals demand an administrative structure on the basis outlined, as a guarantee that they will not be subjected to domination by the local authorities. Such guarantee can readily be provided within the framework of the general scheme outlined in the White Paper. 11 - Financial Arrangements. The financial arrangements of the service, particularly in their application to the voluntary hospitals, are dealt with very briefly in the White Paper, and have clearly not yet received that full and detailed consideration by the government which has been given to the administrative structure. It is not the intention, in this memorandum, to analyse the financial proposals in detail. It is preferable, as with the administrative structure, to confine the issue to main principles. These relate, firstly, to the position of voluntary income and, secondly, to the payments to be made to the hospitals from public funds. 12. - Voluntary Income. In regard to the first, the position is extremely unsatisfactory. At the commencement, the new service was announced as free for all, implying that it would no longer be necessary for any individuals to pay for, or contribute towards, his medical or hospital treatment. Automatically, the impression has become widespread that the voluntary hospitals will no longer require voluntary income by way of contributions, donations or legacies. Then, with ingenuous inconsistency, the White Paper postulated that the voluntary hospitals must continue to rely substantially upon voluntary income, by way of benefactions and voluntary gifts, in order to retain their autonomy and their voluntary status. It would be impossible for such (contd.). 292/847/2/33